The Influence of Sociodemographic Factors on Stress Levels Among Pulmonary Tuberculosis Patients: A Health Belief Model-Based Study - Suhendra Agung Wibowo; Dimas Hadi Prayoga; Ronal Surya Aditya; Apriana Rahmawati; Ifa Nofalia (KHD Production, 2025)
Pulmonary tuberculosis (TB) imposes not only physical but also substantial psychological burdens, particularly stress, which may compromise treatment adherence and outcomes. While the Health Belief Model (HBM) has been widely applied to predict TB treatment behaviors, its utility in explaining how sociodemographic factors shape stress levels remains underexplored. This cross-sectional study aimed to examine the association between sociodemographic characteristics and stress among 150 pulmonary TB patients in Jombang Regency, Indonesia, using the HBM as a theoretical lens. Stress was assessed using the Depression Anxiety Stress Scale–42 (DASS-42), with 62.7% of participants reporting moderate to severe stress. Chi-square and binary logistic regression analyses revealed that education (p = 0.012; OR = 1.89, 95% CI: 1.10–3.25), marital status (p = 0.021; OR = 1.72, 95% CI: 1.05–2.80), and occupation (p = 0.008; OR = 2.45, 95% CI: 1.30–4.60) were significantly associated with stress levels, whereas age and gender were not (p > 0.05). Occupation emerged as the strongest predictor, with unemployed or informally employed patients more than twice as likely to experience high stress. These findings underscore the role of perceived barriers and self-efficacy—core HBM constructs shaped by sociodemographic context—in influencing psychological distress. Integrating tailored psychosocial support into TB care is essential to mitigate stress and enhance treatment success.